Septicemia due to Aeromonas hydrophila in a Pregnant Woman: A Case Report and Review of the Literature - Ricardo Figueroa Damián; Roberto Villagrana Zesati; León Sáinchez Fernáindez; Jose Luis Arredondo García (Hindawi Limited, 1995)
Background: In the late 1960s, the first isolates of Aeromonas were recovered from human specimens. Presently, there is sufficient evidence to suggest that the different isolates of the genus Aeromonas are human pathogens. The most frequent site of infection is the digestive tract, although extraintestinal infection also occurs. In those cases involving septicemia, most infections occur in individuals with underlying diseases. This report presents the case of a pregnant woman with no underlying disease or signs of immunodeficiency who developed A. hydrophila septicemia at 24 weeks gestation.